Panchamahabutha in Naturopathic Medicine: A Classical Review and Contemporary Perspectives - P Y, Shalini; M K, Shradha; Nivetha, B S (Indian Journal of Integrative Medicine, 2025)
Background: Indian philosophy explains the concept of the Panchamahabhuta, or the five element theory (Space, Air, Fire, Water, Earth). These fundamental elements possess distinct qualities and characteristics, forming the basis of both nature and the human body. Objective: This paper aims to trace the historical development of the Panchamahabhuta theory, with an extensive discussion of the fundamental attributes of the five elements (Ether, Air, Fire, Water, and Earth). The study explores the diagnostic and therapeutic methods in Naturopathic Medicine based on the five element theory. Methods: This descriptive study draws upon a variety of informational sources, including ancient texts, books, and articles published in indexed journals accessed through global online databases. Discussion: The balance and harmony of the five elements are vital for the well being of both living and non living entities in the universe. Human health depends on maintaining equilibrium among these elements; any disruption can lead to disease. Each element contains traces of the other four, following a construction order (ether, air, fire, water, earth) and a deconstruction order (earth, water, fire, air, ether). An excess of one element can be corrected by balancing the weaker elements, while deficiencies are addressed by strengthening superior elements alongside the deficient ones. Conclusion: The Panchamahabhuta theory provides a holistic framework for understanding health and disease. By acknowledging the dynamic interplay of elemental forces, naturopaths can develop effective treatments that address the root causes of imbalances. Integrating this ancient wisdom with modern healthcare practices can promote comprehensive and sustainable wellness.